Value-dependent and empathy-mediated: how artificial intelligence-generated marketing content influences customer engagement, and when to disclose its origin - Gao, Xuan; Li, Weiwei; Zhao, Yanli (Frontiers in Psychology, 2026)
The rapid adoption of artificial intelligence-generated marketing content in recent years raises a need for a deeper understanding of its impact on consumer engagement. Moving beyond the traditional focus on technological capabilities, this study examines how artificial intelligence-generated marketing content value (functional vs. hedonic) and credibility jointly influence customer engagement, as well as the psychological pathways involved. Using the Elaboration Likelihood Model and the Cognitive-Affective Processing System (CAPS) framework, two between-subjects experiments (Study 1: N = 152; Study 2: N = 186) were conducted. The results show that: (1) hedonic value elicited higher emotional and behavioral engagement than functional value; (2) a significant interaction emerged between content value and credibility; (3) functional value exerted its indirect effect on engagement through cognitive empathy, whereas hedonic value did so through affective empathy; and (4) crucially, AI disclosure exerted a paradoxical moderating effect, amplifying the cognitive empathy path for functional content but attenuating the affective empathy path for hedonic content. These findings offer a nuanced theoretical framework for understanding the effects of AIGMC and provide managers with actionable insights for implementing value-congruent AI disclosure strategies.